Die verpleegster se terapeutiese funksie - D.C. Harrington; M.E.C. Potgieter (AOSIS, 1980)
Ons sou hierdie praatjie graag wou inlei met Virginia Henderson se definisie van verpleging: " The unique function of the nurse is to assist the individual, sick or well, in the performance of those activities contributing to health or its recovery (or to a peaceful death) that he would perform unaided if he had the necessary will, strength or knowledge. And to do this in such a way as to help him gain independence as rapidly as possible."